PUSAT PELATIHAN NASIONAL ATLET PARALIMPIK DENGAN PENEKANAN AKSESBILITAS ARSITEKTUR DI KARANGANYAR - Herlian, Erwin; Pitana, Titis Srimuda; Daryanto, Tri Joko (Universitas Sebelas Maret Surakarta, 2016)
Indonesia is one country that has great potential in the Paralympic Olympic event. But unfortunately, the potential and achievements are not supported by means of adequate training of Paralympic athletes. Three importants constraints that affect Paralympic athletes are training, a gym and dorm athletes are far apart, the existing sports facilities are public facilities that are less facilitate Paralympic athletes, as well as the city of Solo that it is not possible to accommodate Paralympic athletes training activities. As a problem-solving strategies, takes planning a national training center that can accommodate the needs of Paralympic athletes to improve athletic ability. The training center emphasizes on the design of the facility is accessible for users, especially the Paralympic athletes. Karanganyar selected as the location of the training center because it meets the criteria of the training center. The formulation of the problem in this design is to realize the concept and design of the National Training Center Paralympic Athletes in Karanganyar with Emphasis Architectural Accessibility. Thus it can be formulated National Training Centre planning objectives is to improve and develop the ability of Paralympic athletes in the international arena by emphasizing design accessible to users. The method is carried out to determine the settlement of the problem is through observation at a boarding, training facilities, and the needs of Paralympic athletes and NPC of Indonesia (National Paralympic Committee of Indonesia). Planning national training centers should emphasize the accessibility of architecture in the design of buildings and facilities that are accessible to users. The principle of accessibility architecture is emphasized that security, safety, usability, and independence. Application of these principles appear in the planning design that uses the ramp in all its circulation both inside and in the curved building, the layout of the room and the furniture, the corridors of the building, parking access, handrail, door with universal design, as well as signs and alarms that apply to building national training center. The division of the building into several mass and circulation that connect a response from the existing contours of the site and to emphasize the accessibility of the architectural design.Â Keywords: Accessibility Architecture, Paralympic Athletes, Karanganyar, National Training Center